Differences in duet coordination influence territorial response on a year-round territorial bird species - Sandoval, Luis; Juárez, Roselvy; Bonilla-Badilla, Katherine; Graham, Brendan (Revista de Biología Tropical, 2025)
Introduction: Twelve functions have been assigned to avian vocal duets (e.g., maintaining contact, mate guarding, signaling quality, or resource defense). To separate between functions of duets it is necessary to take into account who is the receiver, the information coded by the sender, and if there is a conflict between pair members. Duets used for resource defense (e.g., territory) are a more aggressive signal than solo songs because they act as a joint defense signal that encode a pairs’ strength or time together in the coordination of both individuals’ song. Therefore, interacting pairs may use duet coordination to respond according to rival information. Objective: Our main objective in this study was to test whether the coordination in time and frequency of White-eared Ground-Sparrow (Melozone leucotis) pair duets influences the territorial response of conspecific pairs. Methods: We recorded 2-5 duets from 31 territorial pairs and measured duet coordination by dividing each ground-sparrow duet into three sections (include sections here) according to each individual’s contribution. In each section we measured frequency range and duration and the difference in frequency range and duration between the introductory and middle section, and the middle and terminal section of each duet. We then used a playback experiments to test pair response to duet coordination. Each pair were exposed to two types of duets: highly coordinated duets and a poorly coordinated duets. Results: We exposed 31 pairs to these two treatments during duet playbacks and measured their territorial response according to the simulated intruders’ duet coordination. We found that pairs that produced highly coordinated duets approached faster and spent more time closer to all playbacks. By comparison, territorial pairs spent more time closer to the poorly coordinated duet stimulus. Total number of vocalization produced in response to duet stimuli were similar between stimuli and independent of the duet coordination of the territorial pairs. Conclusions: Our study indicates that, duet coordination in territorial pairs of White-eared Ground-sparrows is a good predictor of the strength in territorial defense and suggests that pairs used duet coordination to perceive the level of threat from an intruder.